Knowledge, use, and disuse of unconventional food plants - Mayana Lacerda Leal; Rubana Palhares Alves; Natalia Hanazaki (BMC, 2018)
Abstract Background People's diets are usually restricted to a small number of plant species, even in regions with great diversity. We investigated the knowledge of residents in Ribeirão da Ilha, a district of Florianópolis (Santa Catarina, Brazil), about unconventional food plants (UFP). We report the UFP of the region, the parts used, the methods of processing, and the reasons for reduced use or even lack of use. Methods From June 2014 to January 2015, we interviewed 26 long-established residents and made free listings of plant resources in the region. We also did three guided tours, and 24 residents (among the 26) checked pictures of the mentioned plants in order to identify them. Results We identified 63 species distributed in 25 botanical families. Half of the species were mentioned only by one informant. The fruit was the most frequently used part (80% of citations), consumed mainly without processing. Among those species, 27% were used exclusively in the past. The residents attributed non-use to the difficulty in locating the plants and loss of interest in the resource. Conclusion Urbanization and environmental restrictions contribute to the difficulty of access to UFP. Encouraging residents to continue using UFP is necessary to perpetuate this threatened knowledge, promote a more diversified and healthier diet, stimulate a greater interaction among people and nature, and promote on farm conservation of edible plants.